2021
DOI: 10.1016/j.pan.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns and adherence to nutrition guidelines in acute pancreatitis: An international physician survey

Abstract: Background: There is agreement among GI society guidelines for recommending early oral nutrition with non-liquid diet in patients with mild acute pancreatitis (AP). There is less agreement regarding administration of tube feedings (TF) in AP. Data on physicians' adherence to nutrition guidelines and practice variations are limited. Aims: To report practice patterns in the nutritional management of different severity profiles of AP. Methods: We conducted an anonymous electronic survey among physician members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
14
0
3
Order By: Relevance
“…En cuanto al tipo de alimentación con el cuál iniciar, a pesar de las recomendaciones descritas en las guías, un estudio reciente evaluó, mediante una encuesta dirigida a profesionales de la salud, los patrones de práctica actual en el manejo nutricional de la pancreatitis. Los resultados demostraron que 57,3 % inicia la VO con líquidos (claros 40,3 %, completo 17 %) y 21 % con dieta con bajo contenido en grasas (12) . En el presente estudio, 81,8 % de los pacientes inició con líquidos claros, 11 % con dieta sólida con bajo contenido en grasas, 3,6 % con líquidos completos y el 3,6 % restante inició con NE.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En cuanto al tipo de alimentación con el cuál iniciar, a pesar de las recomendaciones descritas en las guías, un estudio reciente evaluó, mediante una encuesta dirigida a profesionales de la salud, los patrones de práctica actual en el manejo nutricional de la pancreatitis. Los resultados demostraron que 57,3 % inicia la VO con líquidos (claros 40,3 %, completo 17 %) y 21 % con dieta con bajo contenido en grasas (12) . En el presente estudio, 81,8 % de los pacientes inició con líquidos claros, 11 % con dieta sólida con bajo contenido en grasas, 3,6 % con líquidos completos y el 3,6 % restante inició con NE.…”
Section: Discussionunclassified
“…Actualmente, no existe base científica que sustente esta hipótesis y se ha demostrado que el inicio precoz de la alimentación (dentro de las primeras 24-48 horas de iniciado el cuadro) mejora el balance nitrogenado, disminuye la incidencia de las infecciones, la mortalidad y la estadía hospitalaria, como consecuencia, la estimulación pancreática generada es mínima. Por tal motivo, las diferentes guías de la práctica clínica recomiendan que los pacientes con PA leve sean alimentados por vía oral (VO) en forma temprana (4,6,12,13) . Sin embargo, hay un subgrupo de pacientes (PA moderada o grave) que desarrollan un estado de hipermetabolismo e inflamación, con un aumento de los requerimientos calórico-proteico y un rápido deterioro nutricional.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As discussed above, there are currently no recommendations for prophylactic antibiotics, and early enteral feeding is recommended due to its protective effect on bowel mucosa integrity and prevents intestinal bacterial translocation. Possible explanations for the lack of compliance may be due to traditional beliefs clinicians have, reluctance for compliance to guidelines or a delay of translation of evidence into personal or institutional protocols[ 133 ]. Hirota et al [ 134 ] in 2014 extracted 10 statements from the Japanese guidelines on AP and classified them into 10 AP bundles for SAP; they showed that patients who had ≥ 8 bundles implemented had lower mortality compared to < 8 bundles (overall 505 patients with SAP, mortality 13.7% vs 7.6%, P = 0.042)[ 134 ].…”
Section: Management Of Non-mild Apmentioning
confidence: 99%
“…For example, the current scoring systems for severity assessment used for acute pancreatitis such as Ranson’s criteria and the Bedside Index of Severity in Acute Pancreatitis (BISAP) score are too complex and need to be repeated after hospitalization. As shown in several surveys ( 6 , 7 ), poor compliance was reported in terms of nutrition and prophylactic antibiotics. Further attempts are necessary to facilitate easy use of guidelines such as pancreatitis bundles provided in the Japanese clinical practice guidelines ( 8 ).…”
mentioning
confidence: 92%